2022
DOI: 10.3389/fpubh.2022.1006536
|View full text |Cite
|
Sign up to set email alerts
|

City-scale assessment of long-term air quality impacts on the respiratory and cardiovascular health

Abstract: BackgroundThe impact of the urban environment on human health is a contemporary subject of environmental research. Air pollution is often considered a leading environmental driver. However, a plethora of other factors within the urban exposome may be involved. At the same time, the resolution of spatial data is also an important facet to consider. Generally, systematic tools for accurate health risk assessment in the urban environment are missing or are not implemented.MethodsThe long-term impact of air qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…For the complete assessment of the effect of air pollution on cardiometabolic health, it would be desirable to also consider the effect of PM 10 and PM 2.5 , however, the variance in their exposure was insufficient, with an interquartile range of 2.90 and 3.75 μg/m 3 , respectively. Similar variance has been observed in previous study from Brno 36 .…”
Section: Methodssupporting
confidence: 92%
“…For the complete assessment of the effect of air pollution on cardiometabolic health, it would be desirable to also consider the effect of PM 10 and PM 2.5 , however, the variance in their exposure was insufficient, with an interquartile range of 2.90 and 3.75 μg/m 3 , respectively. Similar variance has been observed in previous study from Brno 36 .…”
Section: Methodssupporting
confidence: 92%
“…Air pollutants contribute to oxidative injury in the airways, leading to oxidative stress, chronic inflammation, hyperresponsiveness, remodeling, and increased vulnerability to viral infections, exacerbating asthma [4]. After the adjustment of built-up area indicators and socioeconomic indicators, researchers focused on associations with 5-year mean concentrations of nitrogen dioxide (NO 2 ), fine particles with an aerodynamic diameter of ≤2.5 µm (PM 2.5 ), particles with an aerodynamic diameter of ≤10 µm (PM 10 ), and benzene in the city of Brno, Czech Republic [5]. PM 2.5 , PM 10 , and NO 2 significantly impact pediatric respiratory events, including pneumonia, asthma, bronchitis, and acute pharyngitis, in southern Taiwan [6].…”
Section: Introductionmentioning
confidence: 99%
“…Linking exposure to adverse consequences holds significance in assessing exposure and identifying potential health hazards . Some VOCs exhibit mutagenicity, genotoxicity, neurotoxicity, and carcinogenicity. , Epidemiological studies have shown that VOC exposure is associated with various respiratory diseases, such as bronchitis and asthma. , Moreover, exposure to VOCs can induce reactive oxygen species (ROS) or inhibit antioxidant activity, resulting in oxidative stress, which is the underlying mechanism for many noninfectious diseases. , Oxidative stress biomarkers (OSBs) are widely used to detect oxidative stress damage in humans. Nucleic acid is an important target of ROS attack, which has been found to play an important role in the initiation, promotion, and development of diseases .…”
Section: Introductionmentioning
confidence: 99%